POINTS OF ATTACHMENT ON FOOTBALL CLUBS: AN APPLICATION ON "THE BIG FOUR" SUPPORTERS IN TURKISH SUPER LEAGUE - Gizem TOKMAK; Ramazan AKSOY (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Football clubs have to develop brand loyalty on their consumers to survive in the industrialised football sector since loyalty brings psychological and behavioral commitment to the football clubs. Points of attachment is substantial since it involves the factors creating brand loyalty. The degree of interest towards points of attachment of a football club can differ according to demographical factors and the favourableness typologies of the football consumers. In this research, it is aimed to find out if demographical factors and favourableness typologies of the supporters of "The Big Four" in Turkish Super League make any differences on points of attachment. For this purpose, 662 students at Bülent Ecevit University in the spring period of 2013-2014 were reached by using convenience sampling method. Kruskal-Wallis and Mann-Whitney U tests were applied. As a conclusion, it was determined that demographical factors and favourableness typologies created statistically meaningful differences on the points of attachment.